Parent Conferences in the Schools: Procedures for Developing Effective Partnership - Losen, Stuart M.; Diament, Bert; Losen, Joyce Garskof (Allyn and Bacon, 1978)
Keywords: Parent-teacher conferences; dept.psy; faculty_collection

"Facilitation of Stereoscopic Depth Perception by a Relative-Size Cue in Ambiguous Disparity Stereograms": Erratum - Fineman, M.B. (Journal of Experimental Psychology, 1972)
Reports an error in the original article by Mark B. Fineman (Journal of Experimental Psychology, 1971[Oct], 90[2]], 215-221). Fig. 1 and Fig. 2 on pp. 216 and 217 were shown inverted. This mistake made it appear that Stimulus 1 was Stimulus 2, and that Stimulus 3 was Stimulus 4, and that the four stimuli were upside down. (The following abstract of this article originally appeared in record.) Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1972 American Psychological Association.
0 citations (Crossref) [2023-10-31]
Keywords: ambiguous disparity stereograms; dept.psy; relative size cue; stereoscopic depth perception facilitation

The three-dimensional graphic method for quantifying body position - Trochim, William M K (Behavior Research Methods, 1976)
The three-dimensional graphic method for quantifying body position is a series of observer procedures and computer programs designed to yield three-dimensional (height, width, and depth) coordinates for various body points. These coordinates can be graphed by computer in several different ways, and can be analyzed mathematically to provide information about a wide variety of variables, including interpersonal distance and body activity. The procedure for collecting and analyzing the data is explained and the computer programs developed for the method are described. © 1976 Psychonomic Society, Inc.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-192-913-625-728 tex.type: [object Object]
Keywords: dept.psy

The effect of a moving dot transversal on the Poggendorff illusion - Fineman, Mark B; Melingonis, Mark P (Attention Perception & Psychophysics, 1977)
In attempting to derive the minimal component of the Poggendorff figure which would still produce an illusion, responses to three types of transversal were measured. One was the customary solid line type; a second type presented the two segments sequentially, alternating between them; and the third consisted of a moving dot which traveled the transversal path. Each transversal was shown with and without verticals, for a total of six conditions. Ten subjects in each condition adjusted the luminous transversal until the segments appeared to be collinear. Figures with verticals present showed a greater magnitude of illusion than those without, and discrepancies for moving dot transversals were greater than those for comparable solid line figures. Since alternating transversals were not significantly larger than solid line figures, it was concluded that the magnitude of the moving dot effect could not be attributed to temporal sequence. An eyemovement hypothesis was suggested instead. © 1977 Psychonomic Society, Inc.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-262-064-101-166 tex.type: [object Object]
Keywords: dept.psy; normal human; theoretical study; visual illusion

A comparison of the Ponzo illusion with a textural analogue - Fineman, Mark B; Carlson, Jeffrey (Attention Perception & Psychophysics, 1973)
The inappropriate constancy scaling notion of geometric illusions was explored by employing a textural analogue of the Ponzo figure. Ten Ss estimated the length of a horizontal line by equating it with varying companion lines in the context of the Ponzo figure, a textural analogue, and a baseline control in which the lines appeared with no surrounding contours. The textural analogue had the added feature of imposing no contours at the ends of the horizontal lines. It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions. © 1973 Psychonomic Society, Inc.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-215-445-957-250 tex.type: [object Object]
Keywords: dept.psy; normal human; theoretical study; visual illusion

Consequences of transgression: self-punishment and depression. - Wallington, Sue A (Journal of Personality and Social Psychology, 1973)
Assessed the effects of transgression on self-aggression and depression in 96 high school students. Male confederates induced 1/2 of the Ss to transgress by deceiving the E. As a measure of self-aggression all Ss gave themselves electric shocks of intensity which they personally selected. Ss were also given behavioral and subjective-report measures of depression, including the Mood Adjective Check List. Transgressing Ss showed significantly more self-aggression. Transgressing Ss also showed changes on behavioral measures of depression but not on subjective-report measures. Females showed significantly more self-aggression than males regardless of condition. Findings suggest that the altruistic behavior found to occur after transgression may be engaged in for its self-punitive aspect as well as, or rather than as, a means of social restitution, as has been previously suggested. Contrary to the suggestion of some theories of depression, self-punishment did not appear to alleviate depression. (21 ref) (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1973 American Psychological Association.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-375-491-281-980 tex.type: [object Object]
Keywords: Aggression; Depression; Electroshock; Female; Guilt; Human; Male; Morals; Orientation; Personality Inventory; Psychological Theory; Punishment; Self Concept; Sex Factors; Social Behavior; aggression; article; depression; depression; high school students; dept.psy; electric shock; female; guilt; human; male; morality; orientation; personality test; psychological theory; punishment; self concept; sex difference; social behavior; transgression; self-aggression &

The effectiveness of a sex education program on the teacher's sex knowledge and attitudes - Karas, Shawky F; Elliot, Gale Ann (Small Group Research, 1972)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-993-116-130-600 tex.type: [object Object]
Keywords: dept.psy

The influence of communicator-recipient similarity upon the beliefs and behavior of pregnant women - Mazen, Ragaa; Leventhal, Howard (Journal of Experimental Social Psychology, 1972)
A field experiment was conducted to investigate the effects of communicator-recipient similarity and verbal communication upon the attitudes and behavior of pregnant women. Similarity was varied on two dimensions, pregnancy and color; and these factors were crossed with three communication conditions: (1) information on the advantages of rooming-in and breast feeding; (2) information combined with personal endorsement; and (3) no-information control. Both a pilot study and the main experiment showed no important differences in the amount of attitude change or behavioral compliance between the communication conditions. There were also no significant differences in attitude change as a function of similarity in pregnancy. However, a significantly higher proportion of mothers breast fed and roomed-in when the communicator was pregnant and similar than when she was nonpregnant and dissimilar. Similarity in color had no effect upon attitudes or behavior for the topic of rooming-in. But when the communicator was dissimilar in color there was significant negative change in attitudes toward breast feeding. Similarity in color also increased breast feeding. Attitudes and actions were related; mothers with initially favorable attitudes were more likely to comply for both issues. But with only one exception, attitude change was unrelated to behavioral compliance. The results are discussed in terms of visible similarity as a source of information or cues for action. © 1972.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-126-262-556-629 tex.type: [object Object]
Keywords: dept.psy

Facilitation of stereoscopic depth perception by a relative-size cue in ambiguous disparity stereograms. - Fineman, Mark B. (Journal of Experimental Psychology, 1971)
Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1971 American Psychological Association.
2 citations (Crossref) [2023-10-31] tex.ids: pop00125 tex.type: Journal article
Keywords: Conflict (Psychology); Cues; Depth Perception; Female; Form Perception; Human; Male; Reaction Time; Size Perception; Vision; article; association; conflict; dept.psy; depth perception; female; human; male; pattern recognition; perception; reaction time; steroscopic depth perception facilitation; relative-size cue in ambiguous disparity stereograms; vision

Student teachers as tutors for children in an inner city school - Levine, Murray; Dunn, Freda; Brochinsky, Steve; Bradley, Jesse; Donlan, Kay (Child Psychiatry & Human Development, 1970)
A tutoring program for first grade inner city children, employing student teachers as tutors, was developed and evaluated. Tutoring had no discernible effects on performance on the Illinois Test of Psycholinguistic Ability. However, tutored children were placed in the highest reading group, and were rated by the regular classroom teacher as having completed the first grade reading series more often than controls. Tutors saw their children as becoming more responsive over time. Classroom teachers rated the tutored children as more competent in the classroom, more confident, and as viewing the classroom as more benevolent. In contrast to controls, student teachers maintained favorable attitudes toward teaching in the inner city, and they claimed to have benefited in practice teaching from their tutoring experience. However, relatively few actually took teaching positions in inner city schools after completing their training. © 1972 Behavioral Publications, Inc.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-055-959-212-774 tex.type: [object Object]
Keywords: dept.psy

The mental patient and civil rights: Some moral, legal, and ethical considerations. - Tolchin, Gerald; Steinfeld, George; Suchotliff, Leonard (Professional Psychology, 1970)
Distinguishes between legal, ethical, and egalitarian principles involving hospitalization of persons alleged to be mentally ill. With regard to the question of legality, the need for compilation and distribution of relevant information and for informing patients of their rights is discussed. The boundaries of psychologists' professional and personal ethics are viewed as helping patients obtain services which they are personally unable to provide and insuring that the welfare of the patient is placed before the interests of the institution. Egalitarian issues are discussed with regard to: (a) judging whether a mental patient is responsible for his words and actions; (b) the patient's right to accept, reject, or select treatment; and (c) hospitalization of general medical patients and their rights to be informed about their condition, to be notified of test results, and to know the name, quantity, and expected reaction to drugs they are given. It is suggested that psychologists have too long been silent on these issues and in the face of abuses, and that more discussion and stands on them are needed. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1970 American Psychological Association.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-538-943-386-031 tex.type: [object Object]
Keywords: dept.psy; moral vs. legal vs. ethical considerations regarding hospitalization of mentally ill

Premorbid Social Competence and Outcome among Schizophrenic and Nonschizophrenic Patients - Zigler, Edward; Glick, Marion; Marsh, Anna (The Journal of Nervous and Mental Disease, 1979)
The relation between premorbid social competence and outcome was examined with 381 male state hospital patients in four diagnostic categories: schizophrenia, affective reaction, psychoneurotic disorder, and personality disorder. Outcome was assessed using the measures of length of initial hospitaliz
26 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1979HL47900004 tex.unique-id: [object Object]
Keywords: Affective Symptoms; Hospitals; Psychiatric; Human; Length of Stay; Male; Neurotic Disorders; Outcome and Process Assessment (Health Care); Personality Disorders; Prognosis; Schizophrenia; Schizophrenic Psychology; Social Adjustment; Support; U.S. Gov't; P.H.S.; affective neurosis; central nervous system; dept.psy; hospitalization; major clinical study; neurosis; personality disorder; schizophrenia; sociology; therapy

Normal development and psychopathological impairment of the concept of the object on the Rorschach. - Blatt, Sidney J.; Brenneis, C. Brooks; Schimek, Jean G.; Glick, Marion (Journal of Abnormal Psychology, 1976)
103 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976CB12400004 tex.unique-id: [object Object]
Keywords: dept.psy